2017
DOI: 10.1152/ajpregu.00404.2016
|View full text |Cite
|
Sign up to set email alerts
|

Lower-limb hot-water immersion acutely induces beneficial hemodynamic and cardiovascular responses in peripheral arterial disease and healthy, elderly controls

Abstract: Passive heat induces beneficial perfusion profiles, provides substantive cardiovascular strain, and reduces blood pressure, thereby holding potential for healthy and cardiovascular disease populations. The aim of this study was to assess acute responses to passive heat via lower-limb, hot-water immersion in patients with peripheral arterial disease (PAD) and healthy, elderly controls. Eleven patients with PAD (age 71 ± 6 yr, 7 male, 4 female) and 10 controls (age 72 ± 7 yr, 8 male, 2 female) underwent hot-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
91
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 49 publications
4
91
3
Order By: Relevance
“…59 Moreover, Thomas et al have shown that 30 minutes of PH can induce a significant shear stress response and a reduction in mean arterial pressure in patients with peripheral arterial disease. 62 Furthermore, in a healthy cohort who underwent matched duration PH or EX, the PH group demonstrated a greater shear stress response compared to that in response to EX. 60 Based on heart rate responses, the cardiovascular strain in the present study was comparable to that of Thomas et al, which elicited »50% HR max during their immersion protocol.…”
Section: Discussionmentioning
confidence: 96%
“…59 Moreover, Thomas et al have shown that 30 minutes of PH can induce a significant shear stress response and a reduction in mean arterial pressure in patients with peripheral arterial disease. 62 Furthermore, in a healthy cohort who underwent matched duration PH or EX, the PH group demonstrated a greater shear stress response compared to that in response to EX. 60 Based on heart rate responses, the cardiovascular strain in the present study was comparable to that of Thomas et al, which elicited »50% HR max during their immersion protocol.…”
Section: Discussionmentioning
confidence: 96%
“…HT with 42.1 ± 0.6°C of hot water immersion in the lower limb for 30 min also decreases arterial BP, and increases brachial artery blood flow and muscle oxyhaemoglobin in healthy elderly control and PAD patients (Thomas et al . 2017). In a long‐term intervention study, 30 min of a 39°C heat spa with a frequency of 3–5 days/week for 12 weeks induced a greater reduction in systolic BP than exercise intervention (∼90 min supervised gym‐walk per time, 1–2 times/week) (Akerman et al .…”
Section: Discussionmentioning
confidence: 99%
“…3 We examined the acute hemodynamic responses within the upper and lower limbs (to investigate between-limb differences), along with systemic cardiovascular responses to lower-limb hot-water immersion in patients with PAD (n D 11) and in healthy, elderly controls (n D 10). 1 The main findings were as follows: (a) antegrade shear rate in the popliteal artery increased (p < 0.0001) comparably between groups (Controls: C183 § 26%; PAD: C258 § 54%), and (b) lower-limb blood flow increased significantly in both groups, as measured by duplex ultrasound (> 200%). Importantly, the ultrasound-derived increased perfusion was also reflected in two other measures; arterial inflow obtained via venous occlusion plethysmography and indices of oxygenated and total hemoglobin measured by near-infrared spectroscopy.…”
mentioning
confidence: 80%
“…Two studies were published in the last year on the acute responses to passive heat in PAD. 1,5 Our research group pursued a lower-limb hot-water immersion protocol following the initial findings with this in healthy individuals. 3 We examined the acute hemodynamic responses within the upper and lower limbs (to investigate between-limb differences), along with systemic cardiovascular responses to lower-limb hot-water immersion in patients with PAD (n D 11) and in healthy, elderly controls (n D 10).…”
mentioning
confidence: 99%